Open Access in Special Education: A Review of Journal and Publisher Policies. - Fleming, Jesse I.; Cook, Bryan G. (Remedial & Special Education, 2022)
Open-access (OA) options, including preprints and postprints, provide free access to research, accelerate the dissemination of academic work, are associated with increased impact of scholarly work, and may aid in dissemination of null results. However, OA publishing is not an established practice for many special education researchers, and journal and publishers' policies regarding OA are not always clear. In this article, we systematically reviewed OA policies (i.e., regarding preprints, postprints, OA publishing, article processing charges [APCs], and embargo periods) for 51 special education journals and five publishers of special education journals. Most journals provided few policies, only three journals provided information for each OA feature examined, and many journals and publishers reported substantial APCs and embargo periods over 18 months. We recommend journals and publishers clearly post OA policies and reduce APCs to foster broad and open dissemination of special education research.